2021
DOI: 10.3390/agronomy11091685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growing Cycle and Genotype on the Morphometric Properties and Glucosinolates Amount and Profile of Sprouts, Microgreens and Baby Leaves of Broccoli (Brassica oleracea L. var. italica Plenck) and Kale (B. oleracea L. var. acephala DC.)

Abstract: Some new foods (sprouts, microgreens and baby leaf) of the brassica genus are appreciated for their nutritional and nutraceutical values. The aim of this experimental trial was to improve the nutraceutical traits of these foods by evaluating the effects of the climatic condition, genotype, and plant growth stage on the development of greater quality in relation to these new foods. The morphometric and glucosinolates (GLSs) traits of three traditional Italian cultivars of Brassica oleracea crops, such as brocco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
5
0
4
Order By: Relevance
“…The study of B. oleracea plants from the Acephala group, comparing different kale and collard greens, has attracted worldwide attention and recognition of these vegetables as superfoods in recent years which cause significant increase in their production and consumption [11]. This group of cruciferous vegetables is known for their good environmental adaptation and better resistance to unpleasant conditions such as drought, salt stress, or high and low temperatures [19,20]. Consumption of young kale in the form of sprouts, microgreens, and baby leaves is also becoming increasingly popular and has been reported to be a good source of different phytochemicals [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The study of B. oleracea plants from the Acephala group, comparing different kale and collard greens, has attracted worldwide attention and recognition of these vegetables as superfoods in recent years which cause significant increase in their production and consumption [11]. This group of cruciferous vegetables is known for their good environmental adaptation and better resistance to unpleasant conditions such as drought, salt stress, or high and low temperatures [19,20]. Consumption of young kale in the form of sprouts, microgreens, and baby leaves is also becoming increasingly popular and has been reported to be a good source of different phytochemicals [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The expected higher biomass of microgreens was also found in three Brassica oleracea L. cultivars, namely 'Broccolo Nero', 'Cavolo Lacinato Nero di Toscana', and 'Cavolo Broccolo Ramoso Calabrese', whose microgreens had weights on average +240, +125, and +100% compared to the sprouts' weights, respectively [35]. A more recent study from the same research group on the same cultivars [36] confirmed this trend, observing a 211, 119, and 133% increase in the microgreen biomass of 'Broccolo Nero', 'Cavolo Lacinato Nero di Toscana', and 'Cavolo Broccolo Ramoso Calabrese' cultivars compared to the sprouts' biomass, respectively.…”
Section: The Growth Stage Of Sprouts and Microgreens Influences Bioma...mentioning
confidence: 63%
“…A pequena variedade de hortaliça microverdes comercializadas pode influenciar no crescimento da demanda, pois muito consumidores podem não ter preferência pelos produtos disponibilizados atualmente. No mundo, as espécies mais exploradas de microverdes são pertencentes às famílias Brassicaceae, Asteraceae, Chenopodiaceae, Lamiaceae, Apiaceae, Amarillydaceae, Amaranthceae e Cucurbitaceae (KYRIACOU et al, 2016), com destaque para brócolis, couve, rabanete e rúcula da família Brassicaceae (DI BELLA et al, 2021).…”
Section: Resultsunclassified